Photoinduced effects in TiO2 nanocrystalline films with different morphology - Djaoued, Yahia; Ozga, K.; Wojciechowski, A.; Ali H. Reshak, Al-Jaary; Robichaud, J.; Kityk, I. V. (Elsevier B. V., 2010)
Link to publisher's homepage at http://www.elsevier.com/